An evaluation of the libraries in engineering colleges and universities in Metro Manila - Conejo, Fresca P. Bacor 1954-
Findings also revealed that thirteen libraries have weak periodical collections. Libraries did not meet the standard for storage space of seldom used books. Specific recommendations were suggested for possible improvement in the administration and organization of the resources and services of the libraries.